2011
DOI: 10.1177/0022034511399906
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dental Nociceptive Neurons

Abstract: Selective blockade of nociceptive neurons can be achieved by the delivery of permanently charged sodium channel blockers through the pores of nociceptive ion channels. To assess the feasibility of this application in the dental area, we investigated the electrophysiological and neurochemical characteristics of nociceptive dental primary afferent (DPA) neurons. DPA neurons were identified within trigeminal ganglia labeling with a retrograde fluorescent dye applied to the upper molars of adult rats. Electrophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 37 publications
3
58
1
2
Order By: Relevance
“…In rats, labeling of IB4 in TG sections showed that less than 5% of retrogradely labeled dental afferents are IB4-positive (Fried et al, 1989;Yang et al, 2002;Kvinnsland et al, 2004;Gibbs et al, 2011). In contrast, the percentages of IB4-positive pulpal afferents in cultured dental afferents were as high as 75% (Park et al, 2006;Kim et al, 2011). The source of such a discrepancy is not clear.…”
Section: Discussionmentioning
confidence: 98%
“…In rats, labeling of IB4 in TG sections showed that less than 5% of retrogradely labeled dental afferents are IB4-positive (Fried et al, 1989;Yang et al, 2002;Kvinnsland et al, 2004;Gibbs et al, 2011). In contrast, the percentages of IB4-positive pulpal afferents in cultured dental afferents were as high as 75% (Park et al, 2006;Kim et al, 2011). The source of such a discrepancy is not clear.…”
Section: Discussionmentioning
confidence: 98%
“…A combination of molecular [single-cell reverse-transcription polymerase chain reaction (RT-PCR)], immunohistochemical, and functional (patch clamping) studies revealed that most (up to 85%) trigeminal ganglion neurons innervating the tooth pulp express TRPV1 (Park et al, 2006;Kim et al, 2011b). Importantly, these neurons respond to noxious heat (and also capsaicin) with elevated intracellular calcium levels (Chaudhary et al, 2001).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
“…Les canaux thermo-TRP sont représentés par les canaux TRPV (vanilloïde), TRPA (ankyrine) et TRPM (mélastatine). Les canaux TRPV1 et TRPV2, activés par la chaleur, ainsi que les canaux TRPA1 et TRPM8, activés par le froid, ont été identifiés dans les corps cellulaires des neurones trigéminaux à l'origine de l'innervation pulpaire [6]. TRPV1 et TRPV2 sont principalement exprimés par les fibres myélinisées.…”
Section: Diversité Des Afférences Dentaires Primairesunclassified